Zagotavljanje migracijskih koridorjev za prostoživeče živali na območju železniške infrastrukture - Al Sayegh-Petkovšek, Samar (Acta silvae et ligni, 2023)
Rail transport is considered to be more environmentally friendly, economical and socially acceptable than other types of land transport, especially when compared to road transport. However, it can adversely affect wildlife by creating barriers to their movement, commonly known as the “barrier effect”, and by directly increasing mortality due to collisions with trains. Therefore, it is crucial to plan and implement mitigating measures to ensure ecological connectivity and reduce wildlife mortality caused by rail traffic. The primary focus of such measures should be on preventing animals from accessing and lingering on railway tracks, since trains typically cannot avoid collisions. Measures that effectively reduce the number of collisions without exacerbating the barrier effect are particularly desirable. In this review article, we focused on measures that have been proposed or implemented in railway infrastructure. Additionally, we examine recent research exploring the feasibility of alternative mitigation measures, such as warning systems tested in Canada and Sweden. The second part of the paper presents a proposal for a protocol designed to ensure migration corridors and minimize barrier effects. The protocol was developed based on relevant literature and previous studies, as well as our own experience in planning and implementing monitoring measures to reduce wildlife mortality (with a focus on ungulates) on roads, highways and freeways. It also incorporates an analysis of collisions between wildlife and trains on the Slovenian railways network during a selected five-year period.
Keywords: barierni učinek; barrier effect; migracijski koridorji; mitigation measures; omilitveni ukrepi; protocol; protokol; railway infrastructure; trki prostoživečih živali z vlaki; wildlife corridors; wildlife-train collisions; železniška infrastruktura